2021
DOI: 10.1016/j.bjid.2021.101603
|View full text |Cite
|
Sign up to set email alerts
|

Self-prescribed Ivermectin use is associated with a lower rate of seroconversion in health care workers diagnosed with COVID, in a dose-dependent response

Abstract: Background Over-the-counter use of ivermectin amongst other drugs as SARS-CoV-2 treatment has been increasingly common, despite the lack of evidence on its clinical efficacy. Objective To evaluate the effect of ivermectin use on production of antibodies against SARS-CoV-2 in health care workers (HCW) diagnosed with COVID-19 and of Th1/Th2 cytokines by stimulated peripheral blood mononuclear cells of the same cohort (PBMCs). Methods This cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The scenario of fear and anxiety imposed by the new coronavirus pandemic boosted a search for therapeutic and/or prophylactic pharmacological strategies, but the lack of a drug with proven efficacy against SARS-CoV-2 during the first year of the pandemic encouraged the population to use drugs still under evaluation for the virus 14 . However, it was found that abdominal pain, diarrhea, and taste alteration were more frequent among COVID-19 cases who received multiple doses of this drug 15 , and abdominal pain among those who received a single dose 16 . Furthermore, high doses of ivermectin have been associated with hypotension and neurological effects such as decreased consciousness, confusion, hallucinations, seizures, coma, and death 17 .…”
Section: Discussionmentioning
confidence: 96%
“…The scenario of fear and anxiety imposed by the new coronavirus pandemic boosted a search for therapeutic and/or prophylactic pharmacological strategies, but the lack of a drug with proven efficacy against SARS-CoV-2 during the first year of the pandemic encouraged the population to use drugs still under evaluation for the virus 14 . However, it was found that abdominal pain, diarrhea, and taste alteration were more frequent among COVID-19 cases who received multiple doses of this drug 15 , and abdominal pain among those who received a single dose 16 . Furthermore, high doses of ivermectin have been associated with hypotension and neurological effects such as decreased consciousness, confusion, hallucinations, seizures, coma, and death 17 .…”
Section: Discussionmentioning
confidence: 96%
“…20 SM with this compound could lead to ADRs such as abdominal pain, diarrhea, taste alterations, ataxia, orthostatic hypotension, increased transaminases, and vertigo. 21,22 Similarly, ASA has been proposed as a potential therapy in patients with SARS-CoV-2 infection because of the associated risk of coagulopathy seen in some cases of COVID-19. Evidence remains variable: some studies demonstrate a reduced risk of severe COVID-19 with the use of ASA; 23 however, most studies show no effect on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…20 SM with this compound could lead to ADRs such as abdominal pain, diarrhea, taste alterations, ataxia, orthostatic hypotension, increased transaminases, and vertigo. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing the group that took ivermectin, they found that there were no statistically significant differences in clinical severity; however, abdominal pain, diarrhea, and taste alterations were more frequent in those who received multiple doses of this drug. 54 …”
Section: Drug Used For Self-medication In Covid-19mentioning
confidence: 99%